Answer: A
Step-by-step explanation:
(c-2d)(3c-2d)
= 3c^2 - 8dc + 4d^2
Answer:1
1/6 3/12 2/3
Step-by-step explanation:
3/12 = 2/6
2/3 = 4/6
1/6<2/6<2/3
Answer:
x^2+(y-1)^2=25
Step-by-step explanation:
eqn of circle : (x-h)^2+(y-k)^2=r^2
center of circle = (h,k)
hence, the center of the current circle is (2,3)
moving 2 units to the left would make the center (0,1)
the radius would remain the same (5) , hence the new eqn would be
(x-0)^2+(y-1)^2=25
x^2+(y-1)^2=25
Answer:
r≈23.4cm
Step-by-step explanation:
The small dish costs $2 each and the large dish costs $4 each,
2(3)+4(2)=6+8=14
2(4)+4(1)=8+4=12